Introduction to Social Network Research: Brokerage Typology - Anil Kumar Chaudhary; Laura A. Warner (EDIS)
Brokerage occurs constantly in our daily lives. You, an Extension educator, want to deliver a financial management program in two neighborhoods, A and B. Neighborhood A needs help immediately, but you have no connections there. You do have connections in the other neighborhood, and you know that a family in Neighborhood A has friends in Neighborhood B. In this example, the Neighborhood A family can be a broker to help you deliver a program in Neighborhood B. Extension educators can use brokerage typology to understand how information and resources flow among their target audiences, and by identifying the brokers in their local communities, to increase the connectedness of communities and expand the reach of Extension programs to a larger population. This 4-page fact sheet was written by Anil Kumar Chaudhary and Laura A. Warner, and published by the UF Department of Agricultural Education and Communication, March 2015.